Shared visions for marine spatial planning: Insights from Israel, South Africa, and the United Kingdom. (1st April 2022) - Rivers, N.; Truter, H.J.; Strand, M.; Jay, S.; Portman, M.; Lombard, A.T.; Amir, D.; Boyd, A.; Brown, R.L.; Cawthra, H.C.; Faure Beaulieu, N.; Findlay, K.; et al.
Abstract: The online symposium Shared Visions for Marine Spatial Planning: Insights from Israel, South Africa and the United Kingdom was held from 9–10 March 2021. Insights from this multi-disciplinary and international symposium included 1) current states of marine spatial planning (MSP) in the three countries, 2) how MSP can be a helpful tool to advance marine conservation, 3) the use and challenges of geospatial technologies for MSP, 4) how multidisciplinary, interdisciplinary and transdisciplinary efforts can help improve MSP processes and 5) recommendations for effective and collaborative MSP. Key reflections from the symposium included the need for MSP to be multi-, inter- and transdisciplinary in its stakeholder collaborations and aligned with in-country and area contexts. Highlights: To facilitate an adaptive, country-specific MSP process, the acknowledgement of contextual realities and inclusion of all local stakeholders is required Transdisciplinarity is essential for truly collaborative and effective MSP Ecosystem-based approaches to MSP can help advance marine conservation Large scale mapping and modelling is required to inform MSP